(untitled) (Research, Society and Development, 2021)
Objectives: The aim of this study was to evaluate the cytotoxicity and osteogenic potential of experimental medications containing Calcium Hydroxide (CH) and Activated charcoal (AC). Methodology: Osteoblastic (MC3T3) and fibroblastic (L929) cells were cultivated in 96 well plates (1 x 104 cells/well) and, after 24 h, treated with extracts, according to experimental groups [(Experimental groups: C - Control; CH - CH paste; CH+10%AC - experimental paste 1 (CH paste + 10% AC); CH+5%AC - experimental paste 2 (CH paste + 5% AC)]. Cytotoxicity and potential osteogenic was performed by MTT and alkaline phosphatase activity, respectively, after 1, 3 and 7 days. Results: For intergroups comparisons, ANOVA 2 factors were used, followed by Tukey test (p < 0.05). There was no difference among the pastes for cytotoxicity in both cells (p > 0.05). For osteogenic potential, it was found that all experimental groups stimulated mineralization in relation to control group, except for experimental paste 2 at 7 days. Conclusion: The addition of AC to the CH paste does not modify toxicity and osteogenic properties. Add 10% of AC appears to be more effective than 5%.